2005
DOI: 10.1007/s10653-005-0127-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and risk assessment modeling of As and other heavy metals contamination around five abandoned metal mines in Korea

Abstract: Tailings, agricultural soils, vegetables and groundwater samples were collected from abandoned metal mines (Duckum, Dongil, Dongjung, Myoungbong and Songchun mines) in Korea. Total concentrations of arsenic (As) and heavy metals (Cd, Cu, Pb and Zn) were analyzed to investigate the contamination level. Several digestion methods (Toxicity characteristics leaching procedure (TCLP), synthetic precipitation leaching procedure (SPLP), 0.1 N/1 N HCl) and sequential extraction analysis for mine tailings were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 11 publications
1
51
0
2
Order By: Relevance
“…Besides, a maximum As concentration of 53.54 mg kg -1 was observed in MB site, which exceeded the soil contamination concern guideline. Lee et al (2005) reported that the MB mine showed the maximum As concentration of 72.1 mg kg -1 in agricultural soil. On the contrary, the average concentration of As in KK mine was the lowest with 0.08 mg kg -1…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, a maximum As concentration of 53.54 mg kg -1 was observed in MB site, which exceeded the soil contamination concern guideline. Lee et al (2005) reported that the MB mine showed the maximum As concentration of 72.1 mg kg -1 in agricultural soil. On the contrary, the average concentration of As in KK mine was the lowest with 0.08 mg kg -1…”
Section: Resultsmentioning
confidence: 99%
“…Most of abandoned mines developed in the early 20th century have been left without environmental protection (Kim et al, 2005). The tailing is transferred to nearby agricultural lands, and hence contaminates the soil by weathering process and runoff.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk assessment methodology has been recognised as a powerful tool for the decision-making process in contaminated sites management, especially when contamination of soil or water is involved (Suter et al, 2000;US-EPA, 1998). The use of risk assessment techniques in mining activities has mainly focused on human health issues (Kim et al, 2005;Lee et al, 2006). Ecological risk tends to be considered a second priority however to propose remediation techniques or new occupation plans of these contaminated sites is very difficult if the potential risks to biological communities are not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Inlet water pH = 7 Inlet water pH = 8 The release of metals and their environmental fate and transport are a topic of great concern [13][14][15][16]. The relationship between metals in tailings and the surrounding environment and properties of tailings/soil/water have also been widely explored [17,18].…”
Section: Introductionmentioning
confidence: 99%